Palladium-catalysed transfer hydrogenation of alkenes in the presence of zinc powder and various organic acids - I.B. Masesane; P.G. Steel (Bulletin of the Chemical Society of Ethiopia, 2005)
Catalytic transfer hydrogenation using palladium(II) chloride, zinc powder and various organic acids proved effective for the reduction of a variety of alkenes at ambient temperature and atmospheric pressure. The method was found to be convenient, economical and uses a stable nonpyrophoric catalyst.